IoT based hybrid optical-wireless microstructured optical fiber sensor network for cadmium ions detection - Mohammed, Husam Abduldaem; Yaacob, Mohd Hanif (Elsevier B.V., 2025)
The Internet of Things (IoT) has grown rapidly in recent years across several industries, most notably environment monitoring, healthcare, and architecture. A network of various devices is connected by IoT. A smart environment monitoring system that maintains electronic contamination in water records and offers real-time monitoring is required. An IoT based remote monitoring optical fiber sensor network is proposed and developed. The user is notified via the internet anywhere. A reflective taper-in-etch standard single mode fiber (TiESSMF) sensing platform is used for cadmium ion (Cd(II)) remote detection in aqueous solutions and is integrated with IoT. A 2 cm long sensing platform was chemically etched with 40 µm diameter, then tapered over a 1 cm length within the etched region with a 13 µm waist diameter. Palladium/graphite nanofiber (Pd/Gnf) nanocomposite is deposited on the TiESSMF via drop-casting technique to increase its sensitivity to ambient changes. The sensor is evaluated using a solution containing Cd(II) ions with a concentration range from 0.1 to 50 parts per million (ppm) at room temperature. The concentrations of the Cd(II) solution are adjusted to alter the refractive index of the solution and, accordingly, the optical properties of the nanocomposite change. The optical power fluctuates due to the measurement. The sensor's values were 0.0619 dBm/ppm, 22 s for sensitivity, and response time, respectively, and 36 s for recovery time. ESP-32 controller was used to process the data of Cd(II) ions concentrations and IoT purposes. With this system, the user can monitor Cd(II) concentration and receive notifications remotely.